2006
DOI: 10.1110/ps.062391106
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the kinase‐associated domain 1 of mouse microtubule‐associated protein/microtubule affinity‐regulating kinase 3

Abstract: Microtubule-associated protein/microtubule affinity-regulating kinases (MARKs)/PAR-1 are common regulators of cell polarity that are conserved from nematode to human. All of these kinases have a highly conserved C-terminal domain, which is termed the kinase-associated domain 1 (KA1), although its function is unknown. In this study, we determined the solution structure of the KA1 domain of mouse MARK3 by NMR spectroscopy. We found that approximately 50 additional residues preceding the previously defined KA1 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 65 publications
(88 reference statements)
1
40
0
2
Order By: Relevance
“…The ␤ Tyr-267 is juxtaposed to ␥1 aromatic residue, Phe-51 in the mammalian structure (556). The ␣-subunit COOH-terminal fragment forms a discreet ␣-helical/␤-strand domain that shares topology with components of the AMPK-related MARK kinases (499). The Townley structure has provided a clear picture explaining the earlier truncation mutagenesis results that showed that the COOH-terminal 25 residues of ␤ (246 -270) were essential for ␥ binding, whereas ␣ binding required 85 residues ␤ (186 -270) (227) (Fig.…”
Section: Subunit Structuresmentioning
confidence: 99%
“…The ␤ Tyr-267 is juxtaposed to ␥1 aromatic residue, Phe-51 in the mammalian structure (556). The ␣-subunit COOH-terminal fragment forms a discreet ␣-helical/␤-strand domain that shares topology with components of the AMPK-related MARK kinases (499). The Townley structure has provided a clear picture explaining the earlier truncation mutagenesis results that showed that the COOH-terminal 25 residues of ␤ (246 -270) were essential for ␥ binding, whereas ␣ binding required 85 residues ␤ (186 -270) (227) (Fig.…”
Section: Subunit Structuresmentioning
confidence: 99%
“…The SnRK1 RD contains a subdomain of unknown function, the kinase-associated1 (KA1) domain, that was reported in the SnRK3.11/Salt Overly Sensitive2 (SOS2) protein kinase to closely superimpose on the protein phosphatase interaction domain (Sánchez-Barrena et al, 2007), a docking site for the clade A PP2C ABI2 (Ohta et al, 2003). Modeling SnRK1.1 with the structures resolved for the KA1 domain in SnRK3.11 (Sánchez-Barrena et al, 2007), the AMPK-related microtubule-affinity-regulating kinase3 (Tochio et al, 2006), and for AMPKa (Xiao et al, 2011), revealed that in SnRK1.1, this subdomain spans residues 390 to 512 (see Supplemental Figure 2 online). As shown, the KA1 domain was both required and sufficient for the interaction with the phosphatase ( Figure 1A).…”
Section: Abi1 and Pp2ca Interact With The Snrk1 Catalytic Subunitmentioning
confidence: 99%
“…crystallography and NMR spectroscopy, respectively (13,14), whereas the N-terminal header and the central spacer domains appear to be largely disordered (see Fig. 1A).…”
mentioning
confidence: 99%